Implementasi Manajemen Pengembangan Karier Pegawai Negeri Sipil melalui Promosi Jabatan di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Medan - Novelia Putri Erlina Siagian; Muhammad Arifin Nasution (Public Service and Governance Journal, 2025)
One of the activities of ASN management is career development such as promotion. This study aims to analyze the extent to which the implementation of career development management of Civil Servants (PNS) through promotions at the Medan City Personnel and Human Resources Development Agency. The implementation of civil servant career development management in BKPSDM Medan City has been well implemented but there are still obstacles. The method used in this research is descriptive research with a qualitative approach. Data collection was carried out using observation, interview and documentation techniques. The data were analyzed qualitatively using the theory of implementation according to George Edward III using four indicators namely Communication, Resources, Disposition and Bureaucratic Structure. The results of the research conducted show that the promotion process at BKPSDM Medan City has been carried out based on the principles of meritocracy which includes performance appraisal, competence, and employee track records. However, there are some challenges such as lack of competency development training and limited number of assessors who meet the qualifications of certain positions, as well as inadequate networks. To overcome these challenges, BKPSDM has implemented training and technical guidance programs, although implementation still needs to be improved. This study concludes that the implementation of career development management for civil servants through promotion in BKPSDM Medan City has been running quite well, but still requires improvement efforts in terms of career planning and employee empowerment.